Antifungal properties of extracts of Ocimum tenuiflorum and Datura stramonium against some vegetable pathogenic fungi - Shinde, Vidya; Dhale, D A (Journal of Phytology, 2011)
A study was carried out to evaluate the antifungal properties of Ocimum tenuiflorum (also known as Ocimum sanctum) and Datura stramonium extracts on Fusarium oxysporum and Rhizopus stolonifer using the well in agar method. The in vitro studies have been performed by using leaf, stem bark and root bark chloroform, alcoholic and aqueous extracts. All extracts showed antifungal activity. The stem bark alcoholic extract of D. stramonium showed maximum activity; while minimum activity was observed with root aqueous extract of O. tenuiflorum against the fungi under investigation. Results showed that radial growth in all the test organisms was impaired by the addition of the extracts in the culture medium used. The test organisms differed in their reaction to the different extracts but on the whole, growth inhibition increased with the concentration of each extract. The antifungal activity for both the plants and for both the organisms was found is in increasing order i.e. root bark < leaves < stem bark.